(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Посвящается человеку, всей душой посвятившему себя знаниям и науке, незаменимому наставнику и ученому, профессору Г.Ш. Жамбатыровой It is devoted to the person who with all the heart has devoted himself to knowledge and science, the irreplaceable mentor and the scientist, professor G. Sh. Zhambatyrova